Aluminum Nanostructures Enhanced Optical Absorption in Thinfilm Silicon Solar Cells - Singh, Y. P.; Jain, Amit; Kapoor, Avinashi (Recent Innovations in Chemical Engineering, 2018)
Background: Plasmonic light trapping in thin-film crystalline silicon solar cells is numerically investigated using finite-difference time-domain simulations. Method: Enhancement of optical absorption due to the excitation of localized surface plasmons in a periodic arrangement of aluminum nanostructures is analyzed. Result: Broadband photocurrent enhancement in a 1 μm thick silicon film can be observed over the 500-800 nm spectral range of interest. Conclusion: Photocurrent density under Air Mass 1.5 global solar irradiation has been found to be enhanced by up to 40% using aluminum nanostructures with 300 nm width and 100 nm thick. The present work offers a cost-effective plasmonic material for solar cell applications.
Keywords: Thin-film solar cells